“Dog-gras” delusion: case report and brief literature review - Revilla Zúñiga, Joshep (2024)
Capgras Syndrome is one of the delusional misidentification syndromes, the most frequent in this group. It is characterized by the delusional conviction that one or more known people, pets, or inanimate things have been replaced by someone or something identical, that is considered a substitute or impostor. A few cases have been published about this phenomenon involving animals. The case of a 29-year-old male and a non-systematic review of relevant bibliography are reported. The patient had the diagnosis of paranoid schizophrenia and was seen in the emergency department of a mental health institution; psychotic symptoms and Capgras delusions related to his pet were evidenced. His clinical course showed a favorable response to an atypical antipsychotic. Different theories that attempt to explain the Capgras Syndrome extended to animals that have emotional and relevant significance for the patient, are examined. This is the eleventh case reported in the literature of Capgras Syndrome associated with pets. An appropriate exploration in psychotic patients will enable the recognition of this uncommon nosological entity.